2020
DOI: 10.3390/ijerph17134622
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Family Influence the Physical Condition and Health of Children in a Rural Environment?

Abstract: The aim of this cross-sectional study was to assess physical conditions related to health status and establish relationships with influencing factors such as family structure, educational level, and parental professional occupation in the infant stage of three to five years in a rural setting. The sample included 205 children between 3 and 5 years of age from rural areas (<10,000 inhabitants) from the region of Castilla-La Mancha (Spain). Fitness level was measured using the PREFIT battery; influencing fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(106 reference statements)
1
2
0
Order By: Relevance
“…In addition, Kim and Park (37) found that the convenience and diversity of family sports equipment are conducive to increasing children's engagement in sports games and have positive benefits for improving children's physical fitness, which further supports the findings of this study. This study found that the safety of sports and game venues near the family significantly affected children's balance ability, explosive power, sensitivity and coordination, endurance, and speed, which is also consistent with some previous studies (38,39). It is believed that children living in communities with old and damaged game facilities near the home have a significant increase in their aimless wandering time, frequent inappropriate events, and significantly poor performance of healthy physical fitness.…”
Section: Influence Of Family Environment On Children's Healthy Physic...supporting
confidence: 93%
See 1 more Smart Citation
“…In addition, Kim and Park (37) found that the convenience and diversity of family sports equipment are conducive to increasing children's engagement in sports games and have positive benefits for improving children's physical fitness, which further supports the findings of this study. This study found that the safety of sports and game venues near the family significantly affected children's balance ability, explosive power, sensitivity and coordination, endurance, and speed, which is also consistent with some previous studies (38,39). It is believed that children living in communities with old and damaged game facilities near the home have a significant increase in their aimless wandering time, frequent inappropriate events, and significantly poor performance of healthy physical fitness.…”
Section: Influence Of Family Environment On Children's Healthy Physic...supporting
confidence: 93%
“…The acquisition and accumulation of children's various exploratory sports experiences need a sufficient amount of activity stimulation. At the same time, an adequate amount of physical activity is conducive to stimulating children's willingness and motivation to participate in sports activities, and then has a positive effect on the level of healthy physical fitness (38). Although the research on the relationship between children's physical activity and their physical fitness has been widely concerned and valued by the academic community, the research on the relationship between them has always lacked sufficient longitudinal research support.…”
Section: Dual Mediating Effect Of Physical Activitymentioning
confidence: 99%
“…However, PF levels in children depend on several determinants, including socio-cultural and economic factors, and others related to lifestyle, which can vary widely among different states and even within the same country/region [ 35 , 36 , 37 ]. In Italy, a few studies have been carried out since the 1990s in some specific regions [ 26 , 27 , 28 , 29 ], but, to the best of our knowledge, no data are available for the Campania region up to now.…”
Section: Introductionmentioning
confidence: 99%